The pine tree parable - Higgs, Liz Curtis; Munger, Nancy (Nashville : Tommy Nelson, 1997)
A farmer and his wife who grow trees to sell for Christmas give their prized, perfect tree to a poor family who cannot afford to pay for it. Text is interspersed with Bible verses.
3 13 19 20 26 30
Keywords: Generosity -- Fiction; Trees -- Fiction; Christian life -- Fiction; Parables